The dependence of the parametric transformation coefficient of acoustic and optical phonons in doped superlattices on concentration of impurities - Hoang, Dinh Trien (H. : ĐHQGHN, 2017)
The parametric transformation of acoustic and optical phonons in doped superlattices is theoretically studied by using a set of quantum kinetic equations for the phonons. The analytic expression of parametric transformation coefficient of acoustic and optical phonons in doped superlattices is obtained, that depends non-linear on the concentration of impurities. Numerical computations of theoretical results and graph are performed for GaAs:Si/GaAs:Be doped superlattices.